2014
DOI: 10.1002/ccd.25752
|View full text |Cite
|
Sign up to set email alerts
|

Variability of fractional flow reserve according to the methods of hyperemia induction

Abstract: This study suggests that the measurement of FFR is reproducible regardless of the hemodynamic changes, hyperemic agents used, or the route of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…Considering these findings, it might be assumed that lower FFR values after high dose IC adenosine injection are caused by the falsely low automatic FFR measurement phenomenon reported in our study, rather than representing more effective hyperemia. Two recently published studies reported no significant differences between FFR measurements following IC injection or IV infusion of adenosine [26,27]. However, the authors did not precisely report whether they used automatically detected or true steady-state FFR, and FFR was continuously averaged during five cardiac cycles in one trial [26].…”
Section: Classification Mismatch Analysismentioning
confidence: 96%
“…Considering these findings, it might be assumed that lower FFR values after high dose IC adenosine injection are caused by the falsely low automatic FFR measurement phenomenon reported in our study, rather than representing more effective hyperemia. Two recently published studies reported no significant differences between FFR measurements following IC injection or IV infusion of adenosine [26,27]. However, the authors did not precisely report whether they used automatically detected or true steady-state FFR, and FFR was continuously averaged during five cardiac cycles in one trial [26].…”
Section: Classification Mismatch Analysismentioning
confidence: 96%
“…administration of the drug is also permitted. No major differences have been demonstrated in the FFR measurement when comparing the different routes of administration of adenosine [17,18]. As i.v.…”
Section: Pharmacological Hyperemiamentioning
confidence: 98%
“…It is important to note that these substances are much less frequently used and thus, do not often appear in the protocols for large RCTs. However, interestingly, when used to produce hyperemia, they do provide a proper and comparative effect [18].…”
Section: Additional Aspects Of Ffr Measurement In Patients Presentingmentioning
confidence: 99%
“…39,40 However, the chances of securing the same dichotomous treatment recommendation by each method of adenosine administration falls to 78 % at FFR values of approximately 0.80 41 and there is a hyperaemic dose-response relationship seen with intracoronary doses of >60 μg. 42 The route of adenosine administration differs from centre to centre, 43 and while FFR measurement with central administration of intravenous adenosine is considered the gold standard, in the era of transradial PCI, intracoronary or peripheral intravenous administration of adenosine is more practical, although this does give similar FFR results to centrally administered adenosine.…”
Section: Routes and Doses Of Adenosine Administrationmentioning
confidence: 99%